The Role Of Paramedics In Road Traffic Accident Emergencies: A Systematic Review Of Pre-Hospital Care And Patient Outcomes (The Review of Diabetic Studies, 2025)
Road traffic accidents (RTAs) remain a leading cause of mortality and morbidity worldwide, placing significant pressure on emergency medical systems. Paramedics play a critical role in delivering timely and effective pre-hospital care, which is essential for improving patient outcomes. This systematic review aims to evaluate the impact of paramedic interventions on survival rates, response times, and clinical outcomes in RTA emergencies. A comprehensive search of PubMed, Scopus, Web of Science, and Embase was conducted, including studies published between 2015 and 2025. The findings indicate that rapid paramedic response, accurate triage, and early clinical interventions—such as airway management, hemorrhage control, and cardiopulmonary resuscitation—significantly reduce mortality and complications. Additionally, advanced paramedic practices and integration with modern technologies enhance the efficiency of pre-hospital care systems. The review highlights the need for continuous training, standardized protocols, and strengthened emergency infrastructure to optimize trauma care and improve patient survival in road traffic accidents.